INVESTMENT ATTRACTIVENESS OF HOUSING AND UTILITIES SECTOR - P. G. Grabovy (Real Economics Publishing House, 2014)
Investment attractiveness of housing and utilities sector for private operators refers to conditions of investment of communal infrastructure as principles of investment, as well as long-term rent, i.e.: on account of state and municipal assistance on non-return or beneficial terms; possibility to acquire such electricity, heat, water supply and drainage objects being constructed, that have not been included as a part of concession agreement against guarantee of investment return with regard to interest rated specified by such concession agreement, and one of tools of investment attraction thereof is application of new methods of tariff management and various models of agreements.